Aggregate structures analysis of bitumen for the production of modified benders in asphalt industry - Filippelli, Luigi; Bartolino, Roberto; Oliviero Rossi, ,Cesare (My University, 2013)
Since antiquity bitumen had been used as a construction material. Nowadays, most of the huge global production of bitumen each year, are functional to the roads paving industry where they are employed as binders for mineral aggregates to produce asphalt mixes. In the paving industry, a suitable bitumen should be fluid enough at to be pumpable and workable for a uniform covering of the mineral aggregates upon amalgamation. Furthermore, once the asphalt has been laid to build the roads, bitumen has to become sufficiently rigid at the highest pavement temperature to oppose rutting, depending on local climate conditions. Conversely, it must stay flexible enough at the lowest pavement temperature to resist cracking. For these purposes, additives such as polymers, acids, etc., are used to calibrate the operative range of bitumen. In addition asphalt industry is interested to reduce the costs of production, the environmental impact of the production and the safety condition for the paving workers. Bitumen is currently modeled as a dispersion of colloidal particles of asphaltenes, surrounded by a layer of stabilizing polar resins in a continuous oil phase (maltene). Although one can write a very simple definition of bitumen, its chemical composition is very complex and still not completely known. However the characterization of the bituminous materials for its convenient application, is still made by empirical standardized tests. This research project aimed to the deeper understanding of the behavior of bituminous systems, in order to correlate the macroscopic properties to the microstructure of the aggregates that constitute the bitumen colloidal network. We explored the possibility of taking advantage from chemical-physics techniques such as NMR, Rheology and AFM. In particular we have investigated the effect and overall the mechanism through which some chemical additives, already in use by paving companies, explicate their action to modulate the bitumen performances. Several samples different in nature and differently modified were analyzed. The rheological analysis, performed by the measurements under kinematic and dynamic control, helped to determine the material properties related to the structure of the system. The parameters thus obtained, being independent of the measurement conditions may be correlated with the microstructure of the sample investigated by the other techniques we used. As for NMR we exploited the spin-spin relaxation time measurement firstly to find the soften point of bituminous materials whether modified or not. As a novel approach to the understanding of the colloidal nature of the bitumen, the Inverse Laplace Transform (ILT) of the NMR spin-echo decay (T2) was applied. The ILT was used to draw the map of the macro-aggregates inside bitumen at different temperatures providing indication on the nature of the interaction between additives and the colloidal network. The efficiency of the ILT method was proved by atomic force microscopy images. As matter of fact collecting the AFM analysis, the ILT and the rheological results, we were able to describe the correlation between the aggregates at supra-molecular level inside fresh and doped bitumen. This research constituted a new inside bitumen chemistry overcoming the limits of the empirical tests to verify the efficiency of the bitumen modifiers
Scuola di dottorato Scienza e Tecnica "Bernardino Telesio", Scienze e Tecnologie delle Mesofasi e dei Materiali Molecolari, Ciclo XXVI, a.a. 2013
Keywords: Chimica fisica; Bitumi; Reologia